Efek Pemberian Mesenchymal Stem Cell Wharton's Jelly (MSC-WJ) terhadap Gambaran Histologi Pankreas Hewan Model Diabetes Melitus Tipe 1 - Endrinaldi, Endrinaldi; Tofrizal, Tofrizal; Elmatris, Elmatris; Yarni, Sisca Dwi (Majalah Kedokteran Andalas, 2024)
Objective: This study was conducted to determine the effect of administering Mesenchymal Stem Cell Wharton Jelly (MSC-WJ) on the histological appearance of the pancreas of rat in a type 1 diabetes mellitus model. Methods: This research is an experimental research with a Posttest-Only Control Group Design. The sample consisted of 3 groups (Normal, T1DM, T1DM + MSC-WJ). The treatment group was treated with MSC-WJ for 4 weeks. Data analysis used One Way ANOVA and Post Hoc Bonferroni tests. Results: WJ-MSC can increase the mean diameter and area of the islets of Langerhans in the T1DM rat group from 98.08 mm – 126.85 mm and from 4911.95 mm2 – 8995.35 mm2, but this difference is not yet significant (p > 0.05). Conclusion This research shows that there is improvement in pancreatic damage by administering WJ-MSC to diabetic rat due to alloxan induction.